2020
DOI: 10.1016/j.compositesb.2020.107771
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the repeated low-velocity impact behavior of composite laminates

Abstract: The dynamic mechanical responses and damage development of cross-ply composite laminates under repeated low-velocity impact are investigated through finite element simulations with ABAQUS/Explicit. A progressive damage model for laminates, consisting of the continuum damage model, the 3D Hashin failure criterion and the damage evolution model based on equivalent displacement, is integrated with the bilinear traction-separation relationship cohesive model to simulate the damage initiation, evolution and propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 55 publications
3
23
0
Order By: Relevance
“…It can be seen that the two results are in good agreement. Compared to the experimental results, the peak force of the simulation results is 6–10% lower and the impact response time is slightly longer, but this phenomenon can be reasonably explained [10,13]. Furthermore, as can be seen from the comparison of deformation contours of the structures depicted in Figure 5, the FE model is able to reflect the failure modes including debonding, buckling and core compression that occur in the experiments.…”
Section: Numerical Simulationmentioning
confidence: 80%
See 1 more Smart Citation
“…It can be seen that the two results are in good agreement. Compared to the experimental results, the peak force of the simulation results is 6–10% lower and the impact response time is slightly longer, but this phenomenon can be reasonably explained [10,13]. Furthermore, as can be seen from the comparison of deformation contours of the structures depicted in Figure 5, the FE model is able to reflect the failure modes including debonding, buckling and core compression that occur in the experiments.…”
Section: Numerical Simulationmentioning
confidence: 80%
“…To date, a substantial number of works on exploring the impact resistance of metallic and fibre-reinforced thermosetting composite structures have been reported [13][14]. Gibson et al [15] conducted low-velocity impact experiments on glass fiber/epoxy resin composite honeycomb sandwich panels at high impact energy.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, some studies examine the effect of repeated impacts on the mechanical strength of composite materials. Zhou et al [ 32 ] numerically investigated the repeated impact response on carbon/epoxy composite plates in their study. As a result of the study, they observed that the maximum displacement amount of the material increased, and the energy absorption capacity decreased with the increase in the number of impacts applied on the composite plates.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, 35 some preliminary qualitative conclusions of repeated impact on the cross-ply composite laminates were obtained through numerical simulation, whereas the more comprehensive quantitative analysis is still needed through experimental methods. The aim of this study is to investigate the influence of multiple low energy impact on the response of thin cross-ply CFRP laminates.…”
Section: Introductionmentioning
confidence: 99%